2019
DOI: 10.1016/j.red.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Credit, misallocation and productivity growth: A disaggregated analysis

Abstract: We study the effect of credit conditions on the allocation of inputs, and their implications for aggregate TFP growth. For this, we build a new dataset for Mexican manufacturing merging real and financial data at the 4-digit industrial sector level. Using a simple misallocation framework, we find that changes in allocative efficiency account for 75 percent of aggregate TFP variability. We then construct a model of firm behavior with working capital constraints and borrowing limits which generate sub-optimal us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Compared with state-owned enterprises, in non-state-owned enterprises, effective IC has a significant marginal mitigating effect on financial mismatch. Heterogeneity in credit conditions is important in accounting for efficiency gains [ 70 ]. Therefore, the regulators should create a reasonable financial ecological environment, to reduce ownership discrimination in resources allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with state-owned enterprises, in non-state-owned enterprises, effective IC has a significant marginal mitigating effect on financial mismatch. Heterogeneity in credit conditions is important in accounting for efficiency gains [ 70 ]. Therefore, the regulators should create a reasonable financial ecological environment, to reduce ownership discrimination in resources allocation.…”
Section: Discussionmentioning
confidence: 99%
“…That model, among other things, incorporates some dynamics into the one of Schmidt-Eisenlohr (2013). 16 In the framework of Meza, Pratap, and Urrutia (2019) this friction exacerbates a static misallocation of inputs that leads firms to pay a higher interest rates (with respect to the ones that would prevail in the absence of the friction) leading, by definition, to an inefficient allocation of inputs (see Chari, Kehoe, and McGrattan (2007)). last term of the previous equation.…”
Section: Domestic Firms' Problemmentioning
confidence: 99%
“…Whited and Zhao (2019) show that productivity losses can result both from the misallocation of debt and equity and from the misallocation of capital and labour. Meza et al (2019) have shown that interest rates tend to be higher for industries with greater resource misallocation and quantified the impact of credit on static input distortions and total factor productivity (TFP).…”
Section: Motivation and Main Findingsmentioning
confidence: 99%